2011
DOI: 10.1177/102490791101800208
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Diagnosis of Rupture of Brachial Artery Due to Closed Posterior Elbow Dislocation

Abstract: Posterior elbow dislocations complicated with brachial artery rupture are rare, especially in the absence of an accompanying fracture. Severe acute ischaemia is not clearly evident in some cases and the diagnosis of arterial damage may not be realised because the collateral circulation around the elbow might mask signs of acute arterial disruption. We report a patient with brachial artery rupture due to closed posterior elbow dislocation. The diagnosis of arterial injury was delayed because the hand was well p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…As in our case, brachial artery injuries commonly result from a fall on the outstretched hand [19–20] that results in anterior elbow dislocation [21] . They tend to occur in children [4,6,9,12] , although the diagnosis should not be discounted in adults [21–22] .…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…As in our case, brachial artery injuries commonly result from a fall on the outstretched hand [19–20] that results in anterior elbow dislocation [21] . They tend to occur in children [4,6,9,12] , although the diagnosis should not be discounted in adults [21–22] .…”
Section: Discussionsupporting
confidence: 53%
“…They tend to occur in children [4,6,9,12] , although the diagnosis should not be discounted in adults [21–22] . Clinicians should maintain a high index of suspicion for brachial injury when patients present with blunt trauma from a fall onto the elbow coupled with signs suggestive of fracture-dislocation (painful swelling, bruising, loss of contour, and decreased range of motion) and signs of limb ischemia [21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the close proximity of vascular structures to the elbow joint, elbow trauma run the risk of vascular injury especially anterior elbow dislocations or penetrating injuries. 15 Our study showed five cases of vascular injury below 15 years mostly associated with elbow trauma and all recovered well mostly by conservative management. Major vessel injury is a serious complication of military and civilian trauma especially road traffic accident.…”
Section: Discussionsupporting
confidence: 50%